2001
DOI: 10.1159/000047869
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Cultured Rat Islets of Langerhans and Occurrence of Bcl-2, Bak, Bax, Fas and Fas Ligand

Abstract: Isolated Langerhans islets are widely used for diabetic transplantation experiments and investigations of the mechanisms leading to the death or survival of insulin-producing cells in cultured islets. The present study was aimed at investigating programmed cell death and the role of apoptosis-associated peptides in insulin and glucagon cells of islets isolated from untreated rats and held in cultured suspension. Islets were removed from medium on days 0, 7, 14, 21 and 29, embedded in Epon, and semi-thin serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…On the other hand, Bad showed elevated expression across different time points and Bcl-x L was found to increase only at 6 hr hypoxia. Those observations correlate with other studies that showed islets could recover from the isolation procedure with high expression of Bcl-2 during in vitro culture 19 and Bax expression diminished in hypoxic cells. 20 Those findings may indicate hypoxia triggered rescue machinery in islets at the early stage by decreasing proapoptotic genes Bax and increasing anti-apoptotic gene Bcl-2.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Bad showed elevated expression across different time points and Bcl-x L was found to increase only at 6 hr hypoxia. Those observations correlate with other studies that showed islets could recover from the isolation procedure with high expression of Bcl-2 during in vitro culture 19 and Bax expression diminished in hypoxic cells. 20 Those findings may indicate hypoxia triggered rescue machinery in islets at the early stage by decreasing proapoptotic genes Bax and increasing anti-apoptotic gene Bcl-2.…”
Section: Discussionsupporting
confidence: 91%
“…At any one time of tissue sampling, increases in both pro- and anti-apoptotic proteins may be detected, as compensatory responses occur. Similar observations have been previously reported, for example with apoptotic β-cells in cultured and developing rat islets [49], [50] and following serum deprivation in MIN6 β-cells [51]. It is possible, that the milder diabetes that develops in obese VDF rats, when compared to obese ZDF rats, is due to a more robust anti-apoptotic response, since the latter exhibit reduced β-cell bcl-2 levels [35], although we have no direct evidence to support this suggestion.…”
Section: Discussionsupporting
confidence: 91%
“…The proapoptotic proteins Bak and Bax induce apoptosis by interacting with various cellular proteins via their BH3 domains and perhaps by promoting mitochondrial dysfunction, although the precise mechanism is unclear (24). These proteins are present in the rat islet (25,26), and we therefore hypothesized that suppression of their expression via delivery of siRNA duplexes would protect ␤-cells against apoptosis. siRNA duplexes specific for Bax and Bak were individually transfected or transfected in combination into 832/13 cells, resulting in 86 Ϯ 3 and 84 Ϯ 4% decreases in the levels of these proteins, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%